THE IMPORTANCE OF AI IN TEACHING FOREIGN LANGUAGES - Otamuratov Umidbek (Modern American Journals, 2025)
The world of language learning has seen tremendous evolution over the past few decades, from traditional classroom-based instruction to the rise of digital platforms and mobile apps. One of the most significant developments in this space is the integration of Artificial Intelligence (AI). With its ability to process vast amounts of data, adapt to individual needs, and simulate real-life language use, AI is quickly becoming a game-changer in how foreign languages are taught and learned. The infusion of AI technologies into foreign language education not only enhances the efficiency and effectiveness of language acquisition but also creates personalized, dynamic, and immersive learning experiences.This article explores the importance of AI in teaching foreign languages, examining how AI-powered tools are reshaping language education, enhancing learner engagement, and providing opportunities for more personalized and accessible learning experiences. We will delve into specific applications of AI in the language learning process and assess its impact on both learners and educators.
Keywords: AI, personalized learning, one-size-fits-all approach, language platforms, learning systems, feedback, language acquisition, assignments, student progress, individualized instruction, data-driven approach, interactive activities.